PENGARUH PENGELOLAAN SUKU CADANG TERHADAP KELANCARAN OPERASIONAL PADA PT PELAYARAN SAMUDERA RIZQI : Bahasa Indonesia - Pahri Herdiansya; bahasa indonesia; Melia Handayani (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2025)
This study aims to describe the condition of spare parts management and operational smoothness, as well as to analyze the influence of spare parts management on operational smoothness at PT Pelayaran Samudera Rizqi. The research employed a descriptive quantitative approach using a survey method. Data were collected through questionnaires distributed to 60 respondents who are active employees of the company. The descriptive analysis results show that the average score for spare parts management is 4.08 and for operational smoothness is 4.03, both of which fall into the